Everything is Going to Be Okay: Examining the Relationship between Emotion Regulation and Immune Neglect in Affective Forecasting - Patel, Prsni. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Psychology.; Advisor: Heather Urry.; Committee: Elizabeth Race, and Heather Lench.; Keyword: Psychology.